2009
DOI: 10.1302/0301-620x.91b11.22445
|View full text |Cite
|
Sign up to set email alerts
|

The inadequacy of musculoskeletal knowledge after foundation training in the United Kingdom

Abstract: The aim of this study was to determine whether the foundation programme for junior doctors, implemented across the United Kingdom in 2005, provides adequate training in musculoskeletal medicine. We recruited 112 doctors on completion of their foundation programme and assessed them using the Freedman and Bernstein musculoskeletal examination tool. Only 8.9% passed the assessment. Those with exposure to orthopaedics, with a career interest in orthopaedics, and who felt that they had gained adequate exposure to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 17 publications
(25 reference statements)
1
34
0
Order By: Relevance
“…Unfortunately, postgraduate training in the United Kingdom has a similar 1,2015 lack of focus on musculoskeletal medicine. Competency and confidence in musculoskeletal medicine are poor at the completion of the Foundation Programme, a mandatory two-year period of postgraduate training for all U.K. medical school graduates that is typically made up of six four-month placements in various specialties and is designed to "provide generic training that ensures foundation doctors develop and demonstrate…clinical skills for managing patients with both acute and long-term conditions, regardless of the specialty" 10 with only 15% gaining any formal exposure to musculoskeletal medicine and only 8.9% passing the Bernstein and Freedman examination at the completion of the program 11 . Later training in other specific hospital specialties does not provide any musculoskeletal training, and only 0% to 10.5% of vocational training schemes (general practitioner training schemes) in England previously incorporated orthopaedics or rheumatology 9,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, postgraduate training in the United Kingdom has a similar 1,2015 lack of focus on musculoskeletal medicine. Competency and confidence in musculoskeletal medicine are poor at the completion of the Foundation Programme, a mandatory two-year period of postgraduate training for all U.K. medical school graduates that is typically made up of six four-month placements in various specialties and is designed to "provide generic training that ensures foundation doctors develop and demonstrate…clinical skills for managing patients with both acute and long-term conditions, regardless of the specialty" 10 with only 15% gaining any formal exposure to musculoskeletal medicine and only 8.9% passing the Bernstein and Freedman examination at the completion of the program 11 . Later training in other specific hospital specialties does not provide any musculoskeletal training, and only 0% to 10.5% of vocational training schemes (general practitioner training schemes) in England previously incorporated orthopaedics or rheumatology 9,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, graduating medical students become junior doctors and commence a two-year general preregistration period known as the Foundation Programme 10 prior to commencing specialty-specific training. This only provides exposure to musculoskeletal medicine to 15% of graduates for a mean duration of two weeks 11 . At the completion of this program, we showed that only 8.9% have a basic competence in musculoskeletal medicine 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, we used a previously validated examination 7 in musculoskeletal medicine that was designed specifically for medical students and had been used previously in studies in both the U.S. [5][6][7]13,17 and Europe 8,18 . The examination was administered to ninety-two students at the end of the two-week module.…”
Section: Module Assessmentmentioning
confidence: 99%
“…Current evidence suggests that medical student knowledge of musculoskeletal medicine is poor; studies show pass rates of 2% to 25% for medical students using a standardized test [6][7][8][9] . Reports of curricular exposure to musculoskeletal medicine range substantially; in the United States 10 , twenty-five of the 122 schools that were surveyed offered formal training in musculoskeletal medicine.…”
mentioning
confidence: 99%